Neuropathy symptom and change: Inotersen treatment of hereditary transthyretin amyloidosis. Issue 4 (7th August 2020) - Dyck, P. James B.; Coelho, Teresa; Waddington Cruz, Marcia; Brannagan, Thomas H.; Khella, Sami; Karam, Chafic; Berk, John L.; Polydefkis, Michael J.; Kincaid, John C.; Wiesman, Janice F.; Litchy, William J.; Mauermann, Michelle L.; et al.
Abstract: Introduction: Hereditary transthyretin‐mediated amyloidosis (hATTR) manifests as multisystem dysfunction, including progressive polyneuropathy. Inotersen, an antisense oligonucleotide, improved the course of neuropathic impairment in patients with hATTR in the pivotal NEURO‐TTR study (NCT01737398). To determine inotersen's impact on symptoms and patients' neuropathy experience, we performed a post hoc analysis of the Neuropathy Symptoms and Change (NSC) score. Methods: Stage 1 or 2 hATTR patients were randomized to receive weekly subcutaneous inotersen or placebo for 65 weeks. NSC score was assessed at baseline and 35 and 66 weeks. Results: At 66 weeks, inotersen‐treated patients had symptom stabilization as compared with worsening in patients receiving placebo, based on total NSC score. There were also improvements in the subdomains of muscle weakness, sensory, pain, and autonomic symptoms, and for various individual items. Discussion: Inotersen treatment stabilized neuropathy symptoms, including autonomic symptoms, in patients with hATTR according to NSC score. Thus, the NSC may be an effective measure to assess neuropathy progression and patients' neuropathy experience in clinical practice. Abstract : See article on pages 502–508 in this issue .